TEORI PENGIKATAN BAHASA DALAM PEMILIHAN DIKSI UNTUK PENULISAN TUGAS AKHIR MAHASISWA PROGRAM STUDI PERPAJAKAN - , Rusyda Nazhirah Yunus (Universitas Pembangunan Panca Budi, 2020)
This article discusses noun phrase (NP) dirinya which is known as reflexive in Indonesian language. However, this reflexive has an ambiguous reading in a sentence. This is because the NP dirinya can have a reference in a clause as well as outside a clause in the same sentence. As a result, this reflexive disobeyed Principle A. On the other hand, this type of reflexive occasionally is known as a long distance reflexive. Some people had analysed this form of dirinya in a generative framework. They have claimed that the ambiguous reading of this reflexive dirinya was caused by the existence of [+reflexive] and [+pronominal] features which is generated by the NP dirinya at Sstructure. Even though, both of these language experts have argued very convincingly that the reason for the ambiguity of the NP dirinya was because of the different of features that existed on the NP but they didn‟t explain how two readings could have co-existed at the same level in the syntax. This analysis will be argued using the Binding Theory which controls the distribution of NP in a sentence.